The wisdom of Sirach - Wilson, Walter T. (Michigan: William B. Eerdmans publishing company, 2023)
"A commentary on the Book of Sirach in English translation"--
Includes bibliographical references (pages 543-561) and indexes.
Keywords: Bible. -- Commentaries